2019
DOI: 10.1038/s41467-019-13168-4
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylase substrate adenylosuccinate lyase is an oncogenic driver in triple negative breast cancer

Abstract: Protein hydroxylation affects protein stability, activity, and interactome, therefore contributing to various diseases including cancers. However, the transiency of the hydroxylation reaction hinders the identification of hydroxylase substrates. By developing an enzyme-substrate trapping strategy coupled with TAP-TAG or orthogonal GST- purification followed by mass spectrometry, we identify adenylosuccinate lyase (ADSL) as an EglN2 hydroxylase substrate in triple negative breast cancer (TNBC). ADSL expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…Luminal A and Luminal B share similarities in prognosis, while Luminal B have lower expression of hormone receptors, higher expression of proliferation markers, and higher histologic grade than luminal A [17, 18]. Triple-negative breast cancer is defined by aggressive clinical behavior and occurs in 10–15% of sporadic breast cancers [19, 20]. There were 19 (20.21%) TNBC molecular typing patients carried p.Ile1845fs variant.…”
Section: Discussionmentioning
confidence: 99%
“…Luminal A and Luminal B share similarities in prognosis, while Luminal B have lower expression of hormone receptors, higher expression of proliferation markers, and higher histologic grade than luminal A [17, 18]. Triple-negative breast cancer is defined by aggressive clinical behavior and occurs in 10–15% of sporadic breast cancers [19, 20]. There were 19 (20.21%) TNBC molecular typing patients carried p.Ile1845fs variant.…”
Section: Discussionmentioning
confidence: 99%
“…DEC2 sgRNA plasmid and lentivirus are constructed as previously described [ 22 ]. Target sequences were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, non-HIF targets have been identified to be hydroxylated on prolines by PHDs (reviewed in [ 15 ]), resulting in their degradation and/or changes to downstream activity including Centrosomal Protein 192 (CEP192) [ 272 ], Forkhead Box O3 (FOXO3) [ 273 ] and Adenylosuccinate Lyase (ADSL) [ 274 ] by PHD1, Actin Beta (ACTB) by PHD3 [ 275 ], and AKT Serine/Threonine Kinase 1 (AKT1) [ 93 ], TANK Binding Kinase 1 (TBK1) [ 276 ] and Scm-like with Four Malignant Brain Tumour Domains 1 (SFMBT1) [ 277 ] by PHD2 [ 278 ]. Despite these exciting studies, a recent study investigating around 20 of the reported non-HIF substrates, failed to detect any hydroxylation in vitro [ 279 ].…”
Section: Effects Of Hypoxia On Protein Levelsmentioning
confidence: 99%